Association between the Platelet-Derived Growth Factor/Platelet-Derived Growth Factor Receptor System and Risk of Rheumatoid Arthritis: A Systematic Review and Meta-Analysis. (7th March 2022) - Li, Feiyan; Wu, Shaoping; Xie, Hualing; Wang, Wanling; Wang, Jing; Jia, Chanyi; Xie, Chao; Zhang, Xia
Abstract : This research examines the association between the platelet-derived growth factor/platelet-derived growth factor receptor (PDGF/PDGFR) system and rheumatoid arthritis (RA) susceptibility through a comprehensive search of the PubMed database to study the expression of the PDGF/PDGFR system in RA. Review Manager software version 5.3 was used for statistical analysis. Six eligible studies published in the English language were included, including 108 rheumatoid arthritis cases and 85 controls with the corresponding 126 and 97 tests, respectively, relating the expression of the PDGF/PDGFR system to the risk of RA. The overall results indicated a significant association between the PDGF/PDGFR system expression and RA (OR = 5.25, 95% CI: 3.00-9.18, p < 00001 ), RA patients in Asian countries (OR = 4.13, 95% CI = 2.04 -8.39, p < 0.0001 ) and in Western countries (OR = 9.18, 95% CI = 2.04 -8.39, p = 0.03 ), and only PDGF expression in RA patients (OR = 5.28, 95% CI = 2.73 -10.21, p < 0.00001 ). Thus, only the PDGFR expression was insignificantly associated with RA susceptibility (OR = 9.25, 95% CI = 0.63 -136.30, p = 0.11 ). Hence, the PDGF/PDGFR system most likely contributes to susceptibility to RA.